FREQUENCY OF SARCOCYSTIS SP. IN SHEEPDOGS FROM ALPACA ASSOCIATION BREEDERS, MARANGANÍ, CUSCO - Choque M., José (2007)
The aim of the study was to determine the frequency of Sarcocystis spp. in sheepdogs of alpaca farm associations at Maranganí, Cusco, during the dry and rainy season (April 2005 until February 2006). Fecal samples (n = 211) were collected and evaluated using the method of flotation with Sheather solution to observe sporocysts of Sarcocystis spp. The frequency during the dry and rainy season was 42.3 ± 9.2% (47/111) and 72.0 ± 8.8% (72/100) respectively. The results showed an association between the rate of infection and the time of the year (p<0.05), where November had the highest rate (77.8 ± 12.1%, 35/ 45) and March had the lowest (17.6 ± 12.8%, 6/34). In addition, significant difference was found due to age of the dog (p<0.05).